Pengelolaan Sumber Daya Alam di Indonesia: Potensi dan Kebijakan Pemerintah untuk Dukungan Produk Bahan Alam Dengan Daya Anti Bakteri - Lili Andriani (Jurnal Khazanah Intelektual, 2023)
Sembung rambat (Mikania micrantha Kunth) is a traditional medicine of Jambi province from the Orang Rimba (SAD). This plant was used as a medicine for wounds, stomach pain, itching, and diarrheal diseases. Various secondary metabolites in this plant is supported for antibacterial potential. This study aim to determine the antibacterial activity of sembung rambat extract as the local wisdom plant against Propionibacterium acnes and Pseudomonas aeruginosa bacteria. Sembung rambat extract was using 96% ethanol solvent by maceration method and phytochemical screening. Antibacterial activity evaluation were carried out was used disc diffusion methods. The concentrations for evaluation by 10%, 20%, and 30%, positive control was used chloramphenicol 30 μg / disk and negative control in the form of DMSO 10% with 3 times replication. Data analysis was used by One Way ANOVA on SPSS software. The results of the study of sembung rambat extract have the potential to be antibacterial Propionibacterium acnes with an inhibitory zone that belongs to the medium category at concentrations of 10%, 20%, and 30% on average inhibitory zones of 5.87 mm, 6.68 mm, and 9.00 mm. While Pseudomonas aeruginosa provides inhibitory zones of 7.63 mm, 8.22 mm, and 9.25 mm. The proven sembung rambat extract have potential as antibacterial Propionibacterium acnes and Pseudomonas aeruginosa. With this research result, government policy must supported this needed to make policies for natural material products by raising local wisdom plant.